ENGINEERING EDUCATION TODAY: PROBLEMS AND SOLUTIONS - Anatoly A. Alexandrov; Igor B. Fedorov; Valentin E. Medvedev (Высшее образование в России)
The quality of engineering education is the main problem under discussion in the article. Russian method of training engineers, well known in our country and abroad, provides thehighest authority of Russian engineering school in the world. Its basic principles (education based on science and interaction with industry) and characteristics are described. We analyze some negative aspects affecting the quality of engineering education and propose solutions to overcome them. Bauman MSTU offers one of the effective solutions – an organization of pre-university education as a successive system “school – university” including access courses, specialized lyceums and schools, youth scientific programs and Olympiads. Moreover, Bauman University applies the system of additional professional education than enables an engineer to acquire competences in management, intellectual property, communication in foreign languages.